Analisis SWOT Strategi Pemasaran Produk Unit Link Asuransi Syariah (Studi Kasus Pada PT. Sun Life Financial Unit Syariah Cabang Medan) - Anysa Putri; Marliyah Marliyah; Zainarti Zainarti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the Marketing Strategy for Unit Link Sharia Insurance Products at PT. Sun Life Financial Sharia Unit Medan Branch. This study uses qualitative methods, data collection techniques with interview techniques and literature studies. Data were analyzed using the SWOT method to find out the right steps to market Unit Link products to prospective customers. The results of this study indicate that the Medan branch of Sun Life Syariah Unit has dared to compete in a competitive market competition. This can be proven by the existence of a marketing strategy, especially the marketing of Unit Link products implemented by the Sun Life Syariah Unit Medan Branch which includes several strategies, namely personal selling, building a network, providing excellent service or providing satisfactory facilities to increase customer trust and satisfaction, so that Existing customers will not run away from insurance. Based on the results of the SWOT analysis conducted, the company is in quadrant I, which means it must maintain growth and development of the company and not pose a threat to the company itself.